2018
DOI: 10.1213/ane.0000000000003456
|View full text |Cite
|
Sign up to set email alerts
|

Readiness for Discharge After Foot and Ankle Surgery Using Peripheral Nerve Blocks: A Randomized Controlled Trial Comparing Spinal and General Anesthesia as Supplements to Nerve Blocks

Abstract: General anesthesia was associated with earlier readiness for discharge, but the difference may not be clinically significant and did not lead to earlier actual discharge. Most secondary outcomes were not different between groups. The choice of spinal or general anesthesia as an adjunct to peripheral nerve blockade can reflect patient, clinician, and institutional preferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…232 Therefore, peripheral nerve block should be considered for patients without contraindications, either alone or in combination with neuraxial or general anesthesia. 233 Further studies are required to confirm these findings.…”
Section: Intraoperative Measures 6221 | Neuraxial Anesthesia and Peri...mentioning
confidence: 95%
See 1 more Smart Citation
“…232 Therefore, peripheral nerve block should be considered for patients without contraindications, either alone or in combination with neuraxial or general anesthesia. 233 Further studies are required to confirm these findings.…”
Section: Intraoperative Measures 6221 | Neuraxial Anesthesia and Peri...mentioning
confidence: 95%
“…In a small sample trial of patients following esophageal cancer surgery, the combined use of intercostal nerve block was associated with improved cognitive function recovery 232 . Therefore, peripheral nerve block should be considered for patients without contraindications, either alone or in combination with neuraxial or general anesthesia 233 . Further studies are required to confirm these findings.…”
Section: Prevention For Perioperative Ncdsmentioning
confidence: 99%
“…Over the years, numerous studies have shown lower limb orthopaedic surgery as having the highest incidence of pain postoperatively (Chou et al 2008, Chung et al 1997, McGrath et al 2004). LLPNB in this group of patients has been shown to decrease length of stay in recovery, increase patients’ satisfaction and also decrease overall hospital length of stay (YaDeau et al 2018). However, LLPNB is not uniformly performed as part of an anaesthetic technique for lower limb surgery (Corey et al 2014, Johnson et al 2016).…”
Section: Rationale For the Perioperative Acp Involvement In Llpnbmentioning
confidence: 99%
“…Often a combination of spinal and general anaesthesia is used for these procedures. While the therapeutic effect of spinal anaesthesia can be short acting, resulting in severe pain for the patient in recovery, general anaesthesia when given as the sole anaesthetic technique has been shown to result in a higher incidence of pain, postoperative nausea and postoperative vomiting (YaDeau et al 2018, Zhang et al 2022).…”
Section: Rationale For the Perioperative Acp Involvement In Llpnbmentioning
confidence: 99%
“…A meta-analysis performed in 2018 found that patients who received SA prior to total hip arthroplasties required shorter hospitalizations post-operation and reported significantly lower levels of nausea in comparison to patients who underwent GA [ 44 ]. Conversely, a randomized control trial from the same year comparing the outcomes of patients who underwent foot and ankle surgery found that patients who received GA were discharged earlier than those who received SA, while there were no differences regarding reported nausea, opioid use, headaches or back pain [ 45 ]. Additionally, a 2018 study comparing the perioperative and postoperative outcomes of patients who underwent laparoscopic appendectomies found that those who had the procedure performed under SA suffered less surgical field pain and had a longer postoperative pain free period, while also reporting less postoperative nausea and vomiting [ 46 ].…”
Section: Spinal Anaesthesiamentioning
confidence: 99%